The study regarding share of construction on attack of player coordinator, in national volleyball championship youth - Cojocaru, A. M.; Cojocaru, M. (Science, Movement & Health, 2014)
This paper wants to be, if possible, to help all professionals working in the field and beyond. We hope our findings to create an overall picture, even on action game under consideration, unless the game entirely at youth level. The aim of research. Processing and interpretation of official data collected on site during the five days of competition allows us to have a personal view on the level of technical and tactical training of teams and individual players coordinators participating in the tournament for youth. Methods of research. As a working method I used: . information recording method; . interpretation of statistical and mathematical method; . graphical representation method; Results. As can be seen in this chart presents the highest efficiency made lifting to Zone 3, followed closely by lifting the two, these being the areas towards which frequently taking. The area with the lowest efficiency is zone 5, an uncomfortable area for this process, perhaps because those running setting here tend to send up to zone 4, considering that usually found in the two linkage, which owns best technique for attack. Conclusions. Desire and requirement to obtain a positive result and ranked as best lead to a situation where some coaches go over their primary objective: to develop and promote the game of volleyball players for high level. This creates a game based teams practice only on getting the point and not using a complex tactical and technical baggage that can lead to spectacular games default to the objectives stated above.